Performance Evaluation of Energy Efficiency in Dense Heterogeneous Wireless Network - Hengzhi Zhang; Zhongyuan Zhao; Fudong Yang; Yong Li (Dianxin kexue)
In dense heterogeneous wireless network, the large-scale small cell deployment can substantially increase not only the complexity of the interference environment but also the network energy consumption. Based on the system model and deployment scenario of small cell enhancement, the energy efficiency in dense heterogeneous wireless network was analyzed and simulated from the sight of system level under different scenarios with different pico numbers. The evaluation has profound guiding significance for the future energy efficiency analysis and optimization in dense heterogeneous wireless network.